The business plan workbook - Barrow, Colin; Barrow, Paul, 1948-; Brown, Robert, 1937- (London ; Philadelphia : Kogan Page, 2015)
"Equally suitable for academic and professional courses and for those developing small businesses, this book provides 29 assignments that cover all aspects of business planning, from creating a competitive business strategy through to forecasting sales volume and value. The new edition includes new material on the 7 Ps of Marketing, coming up with a winning business idea, strategies for planning growth, and reviewing product or service propositions. Featuring new and updated case studies of real life entrepreneurs, and online resources, this book takes a practical approach to topic of business planning for new venture creation and development"--
"One of the most important steps in launching a new venture or expanding an existing one is the creation of a business plan. Time after time, studies and real-life examples reveal that the absence of a written business plan leads to a higher incidence of failure for new businesses, and inhibits growth and development. Based on methodology developed at Cranfield School of Management, The Business Plan Workbook takes a practical approach to topic of business planning for new venture creation and development. Equally suitable for a range of academic and professional courses and for those developing small businesses, it takes the reader through 29 assignments to help you create and present your business plan, from learning how to create a competitive business strategy through to forecasting sales volume and value. It will help you to validate your business idea, brand your business, research and segment your market, and raise finance; all through one persuasive plan. With new additional material covering the 7 Ps of Marketing, a section of Planning for Growth and a range of new and updated case studies of real life entrepreneurs, this classic text is an invaluable guide to all aspects of business planning"--
Includes bibliographical references and index.
Keywords: Business enterprises -- Finance; Business planning; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Strategic Planning; Print books